2013
DOI: 10.1097/fch.0b013e31828e6733
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pastor Support in a Faith-Based Health Promotion Intervention

Abstract: Pastor support has been viewed as an integral part of successful faith-based health promotion programs; however, few studies have systematically studied these relationships. This study examined associations between pastor support and program-related variables among African American churches taking part in a physical activity and dietary intervention. Results showed that some pastor support-related variables were associated with participant recruitment, retention, and implementation of study requirements, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 34 publications
0
34
1
Order By: Relevance
“…These findings highlight the importance of the pastor in various aspects of a health-related research study and may provide some effective strategies to integrate into future interventions. 75 These difficulties in balancing clergy time and commitment as well as the challenges associated with including lay leaders/volunteers for intervention implementation indicate a greater examination of role of a parish nurse in health promotion, given the documented success with previous research. [76][77][78] Although clergy may play a relevant role in counseling for other non-health-related issues, 17 some evidence has suggested that they may lack self-efficacy for health counseling and may not perceive health-related counseling as being effective approach for improving health behaviors or outcomes.…”
Section: Recommendations For Inclusion Of Clergy In Health Promotion mentioning
confidence: 97%
“…These findings highlight the importance of the pastor in various aspects of a health-related research study and may provide some effective strategies to integrate into future interventions. 75 These difficulties in balancing clergy time and commitment as well as the challenges associated with including lay leaders/volunteers for intervention implementation indicate a greater examination of role of a parish nurse in health promotion, given the documented success with previous research. [76][77][78] Although clergy may play a relevant role in counseling for other non-health-related issues, 17 some evidence has suggested that they may lack self-efficacy for health counseling and may not perceive health-related counseling as being effective approach for improving health behaviors or outcomes.…”
Section: Recommendations For Inclusion Of Clergy In Health Promotion mentioning
confidence: 97%
“…In general, priest support appeared to be critical to implementation effectiveness. Consistent with these findings 40 Baruth, Wilcox, and Saunders found a associations between some pastor support-related variables and participant recruitment, retention, and implementation of study requirement among African American churches. Of the five churches in our sample, Church D was the only “high” implementer church that did not also report high levels of support from the priest.…”
Section: Discussionmentioning
confidence: 56%
“…To date, the implementation strategies used to translate EBIs in faith-based settings have primarily focused on ways pastors can adopt and implement program activities and less on the health practices of the pastors themselves. 68,77 The implementation of PA programs may have more impact and be sustained by church leaders who engage in PA within a supportive organizational climate and culture.…”
Section: Discussionmentioning
confidence: 99%